Computer Vision - ACCV 2006 7th Asian Conference on Computer Vision, Hyderabad, India, January 13-16, 2006, Proceedings, Part I - Narayanan, P.J; Nayar, Shree K.; Shum, Heung-Yeung (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2006)
Welcometothe7thAsianConferenceonComputerVision.Itgivesusgreatpl- sure to bring forth its proceedings. ACCV has been making its rounds through the Asian landscape and came to India this year. We are proud of the technical program we have put together and we hope you enjoy it. Interest in computer vision is increasing and ACCV 2006 attracted about 500 submission. The evaluation team consisted of 27 experts serving as Area Chairs and about 270 reviewers in all. The whole process was conducted electronically in a double-blind manner,a ?rstfor ACCV. Eachpaper wasassignedto an Area Chair who found three competent reviewers for it. We were able to contain the maximum load on the reviewers to nine and the average load to less than six. The review form had space for qualitative and quantitative evaluation of the paper on nine aspects. The submitted reviews underwent an elaborate process. First, they were seen by the Area Chair, who resolved divergences of opinion among reviewers, if any. The Area Chair then wrote qualitative comments and a quantitative score along with his/her initial recommendation on the paper. These were looked at by Program Co-chairs and compiled into a probables list. The Area Chairs and Program Co-chairs met in Beijing during ICCV to discuss this list and arrivedat the ?nal list of 64 oral papers and 128 posters. Naturally, many deserving papers could not be accommodated.